Isolation of Malassezia globosa and M. sympodialis from patients with pityriasis versicolor in Spain - Aspiroz, Carmen; Ara, Mariano; Varea, Marzo; Rezusta, Antonio; Rubio, Carmen (Mycopathologia (1975), 2002)
Pityriasis versicolor is a superficial infection of the stratum corneum by several yeast species formerly collectively named Malasseziafurfur. The genus Malassezia has been recently enlarged with new species. With the exception of M. pachydermatis, the remaining six species have an absolute requirement in vitro for supplementation of long-chain fatty acids in media. These lipophilic yeasts comprise six species: M. furfur, M. globosa, M. obtusa, M. restricta, M. slooffiae and M. sympodialis. The aim of this study was to establish whether there was any association between the various species of Malassezia and pityriasis versicolor lesions. Thus, we studied the isolates from 79 patients with pityriasis versicolor, both from lesions and from apparently healthy skin close to the visible lesions. In pityriasis versicolor lesions, the species most frequently isolated was M. globosa (90%), followed by M. sympodialis (41%). Almost all isolates (99%) belonged to one of these two species. The most frequent pattern was M. globosa as the sole species (58% of cases), although the association with M. sympodialis was also frequent (30%). These results confirmed M. globosa as the main agent of pityriasis versicolor and M. sympodialis as the second agent in importance. Malassezia globosa was found to be a species with high levels of esterase and lipase enzymes of probable importance in their pathogenicity.